Selecting the Type of Grain and Fermentation Conditions to Improve the Nutritional Quality of Grains - Alexandra Meynier; Natalia Rosa-Sibakov; Riikka Juvonen; Pekka Lehtinen; Nesli Sözer; Sophie Vinoy (Proceedings)
Context and Objectives: There is an urgent need for a dietary shift towards an increased consumption of plant protein foods. However, some nutritional and sensory challenges are associated with whole-meal grains and pulses. Fermentation is a promising technology for reducing anti-nutrients, increasing protein digestibility, and reducing starch digestibility in plant-based matrices. This study aimed to evaluate the impact of different fermentation conditions using different bacteria on the nutritional composition of grains and pulses. Methods: Milled wheat, buckwheat, and chickpeas were fermented using different bacteria or combinations of bacteria, i.e., Lactobacillus delbrueckii + Streptococcus thermophilus (Vega), Lacticaseibacillus rhamnosus (Lrham), Leuconostoc pseudomesenteroides (Lpseu), Weissella confusa alone (Wcon) or combined with Lactococcus lactis (Wcon + Lac), or Pediococcus pentosaceus (Wcon + Pen), for 24 or 48 h. Protein hydrolysis and protein and starch digestibility were measured using the O-phtaldialdehyde and Infogest methods, respectively. Starch digestibility was evaluated using the Englyst method. Dietary fibers (DF) were quantified. Results: In buckwheat, all fermentation conditions increased protein hydrolysis, especially Vega. In chickpeas, Lrham and Wcon, alone and in combination, increased protein hydrolysis. In wheat, fermentation did not increase protein hydrolysis. Protein digestibility increased only with Wcon + Pen in buckwheat. For chickpeas and wheat, fermentation did not increase protein hydrolysis, and it was lowest with Lpseu in both cases. Lpseu, Wcon + Lac, and Wcon + Pen led to increased DF in buckwheat, especially soluble high-molecular-weight (HMW) buckwheat (dextran formation). In chickpeas, no increase in DF content was observed due to the hydrolysis of oligosaccharides, but soluble HMW DF increased with Lpseu, Wcon + Lac, and Wcon + Pen (dextran formation). No significant change was observed for wheat DF. The starch hydrolysis index (HI) increased with Lrham over 48 h and Lpseu over 24 h but decreased with Wcon + Lac over 24 h in buckwheat. In chickpeas, HI was reduced in all conditions, the lowest values being with Wcon + Pen and Wcon + Lac. In wheat, HI increased with Lrham over 48 h and decreased with Wcon + Pen. Conclusions: The impact of the fermentation conditions tested differed depending on the grains. Some conditions improved the nutritional characteristics of these grains. These results show promising effects concerning the nutritional quality of grains, which need to be confirmed in finished products.